Polymorphism of CYP2C19 gene polymorphism in Patients with Coronary Heart Disease in Chongqing - Tang, Yishu; Yang, Yang; Wu, Ru; Gao, Miao; Cui, Fang (Archives of Clinical and Biomedical Research, 2018)
Objective: To explore the distribution of drug metabolic enzymes CYP2C19 genetic polymorphism in coronary heart disease (CAD) patients of Chongqing. Methods: We have done genotyping to 179 CAD patients taking clopidogrel by gene chip method, analyzed the distribution of genotype and metabotropic phenotype. Results: In this study, a total of six different CYP2C19 genotypes and three metabotropic phenotypes were detected. The frequency of the homozygous extensive metabolizer phenotype was 32.96% (59/179), the heterozygous extensive metabolizer phenotype was 53.07% (95/179) and the poor metabolizers was 13.96% (25/179). Among the CAD patients in Chongqing, there is no significant statistical difference between these CYP2C19 genotypes and reports in other studies Conclusion: The CYP2C9 gene existed genetic polymorphism in CAD patients in Chongqing, and the distributions of allele frequency and metabolic phenotype frequency are similar to other districts in China.